North Banjarmasin’s distribution pump’s electric energy audit at PT Air Minum Bandarmasih - Monangin, Galvani Amideo; Raharjo, Novi Dwi; Ahmad, Ahmad; Soedjono, Eddy Setiadi (Indonesian Journal of Multidisciplinary Science, 2023)
This study aims to audit the electrical energy of the North Banjarmasin zone distribution pump at the Bandarmasih Drinking Water Company in Banjarmasin City. The case study method was used to find out the description of the problem conditions of the pump installation system and the existing distribution network. The largest electricity consumption is in the operation of distribution pumps. One of the distribution pumps is the Banua Anyar booster pump which serves the North Banjarmasin zone. Electricity consumption during 2022 on the Banua Anyar booster is 1,223,432 kWh at a cost of Rp. 1,521,737,167. The calculation of pump efficiency for the 3 new Banua booster pumps is 57.41%, 55.31% and 44.51% respectively. In this study, the most efficient pump and savings opportunities were obtained by increasing pump efficiency with pump improvements and obtained the financial feasibility of calculating the payback period in the second year with cumulative profit in the fifteenth year of 527,846,868 Rupiah.